On the anti-materialism of the value-form (and its theories): Ontological naturalism and limits to the dialectic of capital - Martín , Facundo Nahuel (2025)
I will try to articulate the antinaturalist theory of the value-form with eco-Marxist ontological naturalism. I will retrace the systematic dialectic of Christopher Arthur. Since it is non-total, this dialectic refers to something external to value, including nature. The anti-naturalistic theory of value, thus, can be situated in an ontologically naturalistic ecological Marxism.